Research on design strategies for wellness towns from the perspective of spatial resilience - Guang-Da Xu; Xiao-Xiao Tong (Journal of Asian Architecture and Building Engineering)
Based on spatial resilience theory, this paper explores strategies for enhancing the design of wellness towns. With the intensification of population aging in China, the wellness industry has experienced significant development opportunities, leading to rapid advancements in wellness town construction. However, the planning and development of wellness towns are currently hindered by issues such as severe homogeneity, limited disturbance resistance, and inadequate functionality, which contribute to increased spatial vulnerability. To address these challenges, this study incorporates spatial resilience theory to establish a spatial resilience evaluation system for wellness towns and proposes corresponding design enhancement strategies. Using the Analytic Hierarchy Process, the spatial resilience evaluation system for wellness towns is constructed, encompassing three dimensions: environment, facilities, and society. Design improvement strategies are proposed in three key areas: enhancing spatial stability, fostering spatial diversity, and establishing spatial recovery capacity. This research provides theoretical guidance for the design and construction of wellness towns, and the proposed spatial resilience evaluation system and design strategies offer practical value. However, given the inherent complexity of spatial planning in wellness towns, future studies should further refine the evaluation index system to enhance the scientific rigor and practical applicability of the research.